Implementasi Kebijakan Ekonomi Hijau Dalam Mendorong Pertumbuhan Ekonomi Inklusif Di Wilayah Berkembang - Gulo, Felix Anugerah (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze how the implementation of green economic policies can serve as a catalyst for inclusive economic growth in developing regions. Using descriptive qualitative methods and a literature review, this study explores the challenges of transitioning from a conventional, extraction-based economy to a sustainable model. Findings indicate that green policies not only improve environmental quality but also create new jobs in the renewable energy and organic agriculture sectors. However, their success depends heavily on regulatory readiness and access to financing.